Predictive Positive Value Xpert MTB/RIF in Detecting Mycobacterium tuberculosis on Adult Pulmonary Tuberculosis Patients in Dr. Soetomo Referral Hospital Surabaya Indonesia - Akirasena, Mayoori; Mertaniasih, Ni Made; Soedarsono; Permatasari, Ariani (Institute of Topical Disease Universitas Airlangga, 2024)
Pulmonary tuberculosis is an infectious disease caused by Mycobacterium tuberculosis (Mtb) and transmitted via droplets. Southeast Asia is the largest contributor of TB, and Indonesia itself has the second-highest number in the world with an incidence of approximately 824000 cases. The most common symptoms of active TB are cough, fever, weight loss, and night sweats. The diagnosis can be established upon the confirmation that one of the specimens contains M. tuberculosis. Xpert MTB/RIF provides results in less than 2 hours, whereas culture takes approximately 2-6 weeks. This research aims to evaluate the characteristics and determine the Predictive Positive Value (PPV) percentage of GeneXpert MTB/RIF, utilizing parameters derived from the gold standard examination results, namely culture. This research method is descriptive- analytic based on secondary data extracted from medical records of patients receiving care at the multi-drug resistant TB (MDR-TB) Outpatient Management at Dr. Soetomo Referral Hospital Surabaya from the period January 2019 – April 2022. The results showed that the PPV level of GeneXpert MTB/RIF in detecting the presence of M. tuberculosis is 90%. The diagnosis of pulmonary TB is also supported by the chest X-ray infiltrate's appearance and clinical symptoms of cough, weight loss, fever, and night sweats. Smoking and diabetes are the most common comorbid and risk factors in TB. The conclusion of this study is that the PPV for diagnosing adult pulmonary TB using the Xpert MTB/RIF is relatively high. This suggests the potential use of this method as a diagnosing tool for accurately diagnosing pulmonary tuberculosis.